Combined use of contact aspiration and the stent retriever technique versus stent retriever alone for recanalization in acute cerebral infarction: the randomized ASTER 2 study protocol. (8th January 2020) - Lapergue, Bertrand; Labreuche, Julien; Blanc, Raphaël; Marnat, Gaultier; Consoli, Arturo; Rodesch, Georges; Saleme, Suzanna; Costalat, Vincent; Bracard, Serge; Desal, Hubert; Duhamel, Alain; Mazighi, Mikael; et al.
Abstract : Rationale: Mechanical thrombectomy (MT) using a stent retriever (SR) device is currently the recommended treatment in ischemic stroke due to anterior circulation large vessel occlusion. Combining contact aspiration (CA) with SR is a promising new treatment, although it was not found to be superior to SR alone as first-line treatment for achieving successful reperfusion. Aim: To determine whether endovascular treatment combining first-line use of CA and SR is more efficient than SR alone. Methods: The ASTER 2 clinical trial is a prospective, randomized, multicenter, open-label trial with a blinded endpoint. We included patients admitted with suspected anterior circulation ischemic stroke secondary to large vessel occlusion <8 hours from symptom onset. They were randomly allocated in a 1:1 ratio to one of two treatment groups (combined CA and SR or SR alone). In the case of failure of the assigned technique after three attempts, other adjunctive techniques were applied. Study outcome: The primary outcome is the rate of successful/complete reperfusion (modified Thrombolysis In Cerebral Infarction (mTICI) score 2c/3) after the entire endovascular procedure. Secondary outcomes include reperfusion rates after the assigned first-line intervention alone and at the end of the procedure, procedural times, change in NIH Stroke Scale score at 24 hours, intracerebral hemorrhage at 24 hours, procedure-related serious adverse events, the modified Rankin Scale score, and all-cause mortality at 90 days and 1 year. The cost effectiveness of the two procedures will also be analyzed. Discussion: This is the first head-to-head randomized trial to directly compare the efficacy of the combined use of CA and SR versus SR alone. This prospective trial aims to demonstrate the synergistic effects of CA and SR devices in first-line endovascular treatment.